Detecting outdoor coexistence as a proxy of infectious contact through magnetometer traces. Issue 19 (1st September 2017) - Kuk, S.; Jeon, Y.; Kim, H.
Abstract : If epidemic contact detection using smartphones can be done with sufficiently fine resolution in outdoor environments, so that those who were within the transmissible distance from an infected person may be identified as a potential infected is explored. The smartphone GPS, at least in its current capacity, is not useful to determine the coexistence within a couple meters that is critical for infectious disease transmission is shown. As an alternative, the usage of magnetometers is proposed, which enables the coexistence determination with the required precision, with much less energy consumption than GPS, and with an added bonus of indoor usability.